THE NURSE-LEADER IN THE MANAGEMENT OF RISK FOR THE PREVENTION AND CONTROL OF INFECTIONS IN PATIENTS WITH CANCER - Nádia Fontoura Sanhudo; Marléa Chagas Moreira (Universidade Federal do Paraná, 2016)
This study aimed to develop nursing leadership strategies directed towards the incorporation of measures for the prevention and control of healthcare-associated infectionsin patients with cancer. It involvedConvergent Care Researchundertaken in an interactive process with nine nurses, in 2013, in an oncological hospital in the interior of Minas Gerais, with treatment of the data through software. Five classes emerged, representing the tendencies of the strategies. Class 1: the presence of the nurse-leader in the inpatient departments; class 2: the work process of the nurse-leader; class 3: handwashing; class 4: the nurse of the hospital infection control committee as a partner of the nurse-leader; and class 5: the promotion of knowledge regarding infections for the nursing team. For the nurses, the elaboration of the leadership strategies is a bet used according to the situation, in order to take account of the unpredictability present in the context and the need to adopt an educational attitude.